POLA KOMUNIKASI KELUARGA HUBUNGANNYA DENGAN PEMBENTUKAN PERSONALITI REMAJA - Anuar, Nurfadzlieyana Azmiera; Abdullah, Norhasima (Jurnal ’Ulwan, 2023)
This study conducted at SMK Meru aims to identify the relationship between family communication pattern and the formation of adolescent’s personality among students of form four and form five in that school as well as to identify the differences in the formation of adolescents’ personality based on aspects of gender, age and number of siblings. This survey has been conducted towards 210 students among form four and form five in SMK Meru. The study was conducted using quantitative methods and survey methods. The instruments used were The Inventory of Family Communication Pattern (RFCP) and Big Five Personality-10 (BFI-10). The data was analyzed through descriptive and inference statistics that includes Pearson Correlation, T-test and Anova via Statistical Packages for Social Sciences (SPSS) version 25.0. the result shows that there is a significant relationship between the family communication pattern and the formation of adolescent’s personality (r = .250, .000 k < .05). Meanwhile, there is no significant difference in the formation of adolescent’s personality based on gender (t = .070, .944 k > .05) and likewise in the aspect of age where there is no significant difference with the value (t = -.967, .226 k > .05). While the last hypothesis shows a finding that there is a significant difference in the formation of adolescent’s personality based on the number of siblings (f = 2.905, .036 k < .05). Therefore, the implications of this study are expected to help several parties such as parents, teachers, the community and as well as for the teenagers themselves about the importance of having a good communication pattern in the family structure to ensure that the future generation of teenagers grow up with outstanding personalities and capable to compete in the future.